CURe-Mi mobile manipulator robot for contact-less COVID-19 patients serving missions - Rokhim, Ismail; Ramadhan, Nur Jamiludin; Najakh, Zainun (Institute of Advanced Engineering and Science, 2023)
Since March 2020, coronavirus disease (COVID-19) has become a major global concern. Even in an emergency, medical personnel should avoid contact with COVID-19 patients. Mobile manipulators are a non-contact alternative to medical personnel for performing healthcare tasks such as distributing supplies to COVID-19-quarantined patients. In this study, patients use an Android application to order mobile manipulator robots, which include the Collaborative Manipulator Robot UR5e and the autonomous mobile robot MiR200 (abbreviated and referred to as CURe-Mi). The HTTP protocol is used for communication between the Android application and the robot. The experiment was conducted in a small room with several tables and bottles used to simulate hospital rooms and medications. The delivery testing results show that all four items were delivered successfully. The results of the manipulator robot and mobile robot movement accuracy tests show that the average error is 0.213 and 4.51 cm, respectively. The Android application performance test demonstrates that the application successfully sends commands to the mobile manipulator robot within its maximum range of 1,800 cm. The CURe-Mi mobile manipulator robot has successfully assisted medical personnel in handling several contactless COVID-19 patients serving missions.